Effects of Self-Selected Exercise on Strength in Charcot–Marie–Tooth Disease Subtypes. (3rd July 2017) - Djordjevic, Djurdja; Fell, Sabrina; Baker, Steven
Abstract: Background: Preliminary studies have supported the utility of exercise as a treatment for Charcot–Marie–Tooth disease (CMT) patients. Despite being the most common inherited neuropathy, there remains a paucity of guidelines for CMT management. Methods: A retrospective chart review was performed on 297 CMT patients. Self-reported exercise and strength results from standardized dynamometer testing were obtained from adult patients' first visits. Values were converted and analyzed based on previously reported age- and sex-matched normative values. Results: Participants with CMT2 had greater strength values than those with CMT1 in hand grip, elbow flexion, and dorsiflexion ( p <0.05). Participants with CMT1 and CMT2 who exercised were statistically significantly stronger in elbow flexion and dorsiflexion than those who did not exercise. Conclusions: These preliminary results suggest that self-directed exercise is associated with greater strength in CMT patients of both CMT1 and CMT2 subtypes. Self-directed exercise may be a convenient, sustainable, and effective method of improving strength and decreasing disability in this population. Future research should explore the type of exercise prescription that best addresses the needs of the CMT population. RÉSUMÉ: Effets sur la force d'exercices choisis par le patient dans différents sous-types de la maladie de Charcot-Marie-Tooth. Contexte: Des études préliminaires ont attesté l'utilité de l'exercice comme traitement des patients atteints de la maladie de Charcot-Marie-Tooth (CMT). Bien que cette maladie soit la neuropathie héréditaire la plus fréquente, il existe peu de lignes directrices quant à son traitement. Méthodologie: Nous avons effectué une revue rétrospective des dossiers de 297 patients atteints de CMT. Nous avons relevé l'information rapportée par les patients adultes lors de leur première visite concernant l'exercice et les résultats d'épreuves de force standardisées au dynamomètre. Les valeurs ont été converties et analysées selon les valeurs normatives rapportées antérieurement, appariées pour l'âge et le sexe. Résultats: Les participants atteints de CMT2 avaient des valeurs de force supérieures à celles des patients atteints de CMT1 aux tests de préhension manuelle, de flexion du coude et de dorsiflexion (p<0.05). La force à la flexion du coude et à la dorsiflexion était significativement plus élevée chez les patients atteints de CMT1 et de CMT2 qui faisaient de l'exercice par rapport à ceux qui n'en faisaient pas. Conclusions: Selon ces résultats préliminaires, l'exercice autogéré est associé à une plus grande force physique chez les patients atteints de CMT, que ce soit CMT1 ou CMT2. L'exercice choisi par le sujet peut être une option pratique, durable et efficace d'améliorer la force et de diminuer l'invalidité dans cette population. De nouvelles études devraient explorer le type d'exercice qui satisfait le mieux les besoins des patients atteints de CMT.